Sistem Aplikasi Manajemen Rental DVD Pada Toko “JKL” - Dwi Yulistyanti (INFORMAL: Informatics Journal, 2016)
Currently very rapid development of technology systems, payroll information system is usually applied in an organization that is done using computers as the main tools in helping achieve the objectives of the organization, company or institution where relevant. No exception SME agencies that currently enjoy doing a lot of young entrepreneurs. Rental VCD and DVD is an attempt to borrow a DVD movie in the form of a strip that eventually the rental will lend to borrowers and given the range of time for merka borrowing and given the cost of borrowing is already in the set. Rental VCDs and DVDs themselves have enough fans among the community itself. This is due to see a lot of people want a movie film original and not pirated. Because if you see the pirated in terms of quality, sound, and so very not good so it becomes less attractive seen. Shops "JKL" itself presents films which are original in terms of quality is very mempuni to be enjoyed by the public. But in its management processes are still using paper and not computerized. By because it Shop "JKL" want to create computer applications to overcome it. Which later can be arranged neatly in its management. In making this application applied his design method is DFD (Data Flow Diagram) and using the JAVA programming language and MySQL as the database editor. The final results were achieved from this research has been the establishment of a computerized system either in the process of data storage and transaction reports.